The effects of physiotherapy and rehabilitation on Pallister-Killian Syndrome: A case report - Topcu, Zehra Guchan; Uzuner, Selma (Journal of Sports Medicine and Therapy, 2018)
The aim of the paper is to determine the effects of physiotherapy and rehabilitation (PHTR) on a child with Pallister-Killian Syndrome (PKS). Gross Motor Function Measure (GMFM) and duration of grasping ping pong ball were the primary outcome measures which were conducted at the beginning, 12th, and 24th month. Neurodevelopmental Therapy and Sensory Integration Therapy were used as intervention methods. The most increase with around 50% was acquired in Section A of the GMFM. Duration of holding a ping pong ball gradually increased. As a result, this is the first paper presenting a PHTR shedule and its results in a child with PKS.